2017
DOI: 10.1016/j.atmosenv.2017.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced levels of atmospheric low-molecular weight monocarboxylic acids in gas and particulates over Mt. Tai, North China, during field burning of agricultural wastes

Abstract: We determined gaseous and particulate C 1-C 10 monocarboxylic acids over Mt. Tai. Formic (C 1) and acetic (C 2) acids were dominant followed by lactic acid. High concentrations of C 1 and C 2 were observed during field burning of wheat straw. High particle-phase fractions of C 1 (0.50) and C 2 (0.31) were observed. Field burning of agricultural wastes is an important source of monocarboxylic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 59 publications
1
20
2
Order By: Relevance
“…For MCAs, H emp ranged between 4.5 × 10 9 mol L −1 atm −1 for pyruvic acid and 2.2 × 10 10 mol L −1 atm −1 for glycolic acid. The values for DCAs were roughly one order of 61 Andreae et al, 85 Mochizuki et al, 79 Miyazaki et al, 86 Kawamura et al, 80 Fisseha et al, 87 79 Miyazaki et al, 86 Kawamura et al, 80 Fisseha et al, 87 Mochizuki et al, 10 A comparison of the calculated H emp values was performed with published temperature-dependent Henry's law constants (H lit ), which were typically determined in laboratory studies and by estimations. However, it is important to note here that H lit values were determined for dilute aqueous conditions, whereas atmospheric particles can be composed of concentrated aqueous and organic phases as well as solids, which may have a significant influence on H emp if substantial fractions of organic acids reside in phases other than the aqueous particle phase.…”
Section: T H I S C O N T E N T I S O N L Y L I C E N S E D F O R C O ...mentioning
confidence: 93%
See 1 more Smart Citation
“…For MCAs, H emp ranged between 4.5 × 10 9 mol L −1 atm −1 for pyruvic acid and 2.2 × 10 10 mol L −1 atm −1 for glycolic acid. The values for DCAs were roughly one order of 61 Andreae et al, 85 Mochizuki et al, 79 Miyazaki et al, 86 Kawamura et al, 80 Fisseha et al, 87 79 Miyazaki et al, 86 Kawamura et al, 80 Fisseha et al, 87 Mochizuki et al, 10 A comparison of the calculated H emp values was performed with published temperature-dependent Henry's law constants (H lit ), which were typically determined in laboratory studies and by estimations. However, it is important to note here that H lit values were determined for dilute aqueous conditions, whereas atmospheric particles can be composed of concentrated aqueous and organic phases as well as solids, which may have a significant influence on H emp if substantial fractions of organic acids reside in phases other than the aqueous particle phase.…”
Section: T H I S C O N T E N T I S O N L Y L I C E N S E D F O R C O ...mentioning
confidence: 93%
“…The particle-phase fractions ε of the organic compounds were calculated by where [X] gas and [X] part represent the concentrations of a specific compound in the gas and particle phase, respectively. Values of ε above 0.5 indicate a stronger partitioning toward the particle phase, while ε values below 0.5 imply a larger presence in the gas phase.…”
Section: Methodsmentioning
confidence: 99%
“…We confirmed that lactic acid is abundantly present in the forest soil from central Japan (1860 ng g −1 wet soil ), but isopentanoic acid is below the detection limit (Kunwar et al, unpublished data, 2018). Lactic acid is produced not only by bacteria (lactobacillus) (Cabredo et al, 2009) but also by the oxidation of isoprene with ozone (Nguyen et al, 2010). The microflora community in soil system may be different between the two sites: a soil-sampling site in central Japan and an air-sampling site in northern Japan.…”
Section: Possible Sources Of Lmw Monoacidsmentioning
confidence: 99%
“…Although such artifacts are possible for any filter-based measurements for ambient conditions, these effects are limited (Kawamura et al, 1985). LMW monoacids were determined as p-bromophenacyl esters using a capillary gas chromatograph equipped with a flame ionization detector (GC-FID) and GC-mass spectrometer (GC-MS) (Kawamura and Kaplan, 1984;Mochizuki et al, 2017a). Briefly, an aliquot of filter (4.3 cm 2 ) was extracted for water-soluble organic compounds with ultrapure water (resistivity of > 18.2 MΩ cm) under ultrasonication.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study on organic acids, normal (C1-C10), branched chain (iC4-iC6), and hydroxy (lactic and glycolic) monoacids were detected in gas, aerosol and snow pit samples (Kawamura et al, 2000;Mochizuki et al, 2016;2017a). In particular, branched chain (iC5) and hydroxy (lactic) monoacids were abundantly detected in aerosol samples from North East China (Mochizuki et al, 2017a). Detected branched chain (iC4 and iC5) and hydroxy (lactic) monoacids are derived from microorganisms and plant tissues.…”
mentioning
confidence: 95%